Contemporary Issues in Strategic Marketing - Ahmet Kemal Şekerkaya (Istanbul University Press, 2020)
There are a large number of factors which may cause markets to evolve. In a market ecosystem, a marketer's job is to create and sustain a business that is meant to be strong, agile, and sustainable enough to survive even in the fastest-changing environment. Thus successful strategy development is crucial for a marketing manager just as it is for a manager at the top management level. Marketing carries the roles of strategic thinking, planning, and management by leading, creating, and providing energy as a power center to many organizations. A marketer has to have the vision to develop not just business, but also functional and operational strategies as well as marketing actions, constantly adjusting them all for the better. Affected by both unwanted changes and/or desired developments in many circumstances, we observe today that the marketers who aim to create value are looking for different and more sustainable competitive methods. This helps businesses gain a relative advantage in the market. New trends are emerging with the help of technological developments which are affecting customers, cultures and values, the economy, budget limitations, other restrictions regarding businesses, and so on. Thus, marketing management needs to take a fresh look at market strategy development and implementation. The ideas that could change the way businesses do their job could arise from both inside and outside the company, including different markets and trends, practices of rivals or studies of marketing academia. Following this notion, we aimed to create a work that would provide a comprehensive review and a discussion of what is new and important for today and for the future in marketing ecosystems. With this book (Contemporary Issues in Strategic Marketing), our intention is to share the valuable ideas of esteemed marketing scholars and experts on the latest and most-valued concepts and developments in different sectors, particularly concerning the competitive marketing landscape in different markets around the world. All the work in this book has been developed by marketing scholars and/or experts and peer-reviewed by a different group of established scholars. The book is thought to be valued and appreciated by both academia and practitioners. Aiming to present the development of new trends, tools, and concepts in the global marketing area, this book has world-wide contributors, consisting of 11 different respected authors from 4 different countries, which are Turkey, the United States of America, Australia and Kyrgyzstan. We attached particular importance to the inclusion of a diverse collection of expert ideas and perspectives from around the world, while also allowing for the subject area to be wide. The book is organized into 9 chapters. It covers many facets in an attempt to understand the most popular current trends for areas of marketing strategy development. It provides insights both for academia and also for marketing managers and/or for entrepreneurs in terms of discussions into different aspects of marketing strategy development, addressing mainly the following contemporary issues in a single and/or a diverse collection of markets. The book includes a chapter on Brand Management Strategies and Challenges, which is crucial for contemporary markets. Advantages and disadvantages of various branding strategies, traditional vs. digital media and their importance for branding and the future of branding are topics which are widely discussed in this chapter. Another chapter is the review on the then and now of Customer Management: From Past to the Future. Components and applications of customer relationship management in different sectors, new technologies affecting customer relationship management, big data as a source of information, and new formats of customer relationship management are discussed in this chapter. Entrepreneurial Marketing is the emphasis of another chapter, as we see lots of new businesses and new business are